2022
DOI: 10.3390/jcm11247466
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Depression, and Anxiety in Patients with COPD, Asthma and Asthma-COPD Overlap

Abstract: Introduction. Asthma and COPD are extremely common respiratory diseases that have a serious impact on people’s lives around the world. A disease characterized by symptoms characteristic for asthma and COPD is called asthma-COPD overlap (ACO). Fatigue and certain psychological disorders such as anxiety and depression are important comorbidities in these diseases. The purpose of this study was to assess the prevalence of fatigue, anxiety, and depression in patients with asthma, COPD, and ACO and to also consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Paying attention to the mental health of ACO patients, this study found that there was a higher proportion of people suffering from depressive disorders in the ACO group than in the asthma-only group, COPD-only group, non-asthma/COPD group, and non-ACO group. Using non-ACO participants as reference, these results revealed that ACO patients might have a higher risk of experiencing depressive disorders, which were consistent with the insights given by previous studies, e.g., Homętowska et al (2022) [ 71 ] and Kang et al (2019) [ 70 ], Chabowski et al (2016) [ 72 ], and Lee et al (2021) [ 15 ]. Although the present findings did not provide definitive evidence of the causal relationship between ACO and depressive states or conclusive reasons for the elevated risks of depression in ACO patients, several factors may contribute to this association.…”
Section: Discussionsupporting
confidence: 89%
“…Paying attention to the mental health of ACO patients, this study found that there was a higher proportion of people suffering from depressive disorders in the ACO group than in the asthma-only group, COPD-only group, non-asthma/COPD group, and non-ACO group. Using non-ACO participants as reference, these results revealed that ACO patients might have a higher risk of experiencing depressive disorders, which were consistent with the insights given by previous studies, e.g., Homętowska et al (2022) [ 71 ] and Kang et al (2019) [ 70 ], Chabowski et al (2016) [ 72 ], and Lee et al (2021) [ 15 ]. Although the present findings did not provide definitive evidence of the causal relationship between ACO and depressive states or conclusive reasons for the elevated risks of depression in ACO patients, several factors may contribute to this association.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, there is a close association between mental health and respiratory diseases. For instance, patients with COPD and asthma are more likely to experience anxiety and depression ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of chronic respiratory symptoms in a young patient should begin by evaluating a diagnosis of asthma [ 39 ]. Additionally, the combination of the two diagnoses in a single patient constitutes a challenge for the clinician, especially at younger ages, with direct clinical consequences [ 40 , 41 ]. Yet another consideration is that few patients in this age group have been included in large clinical trials.…”
Section: Young Copdmentioning
confidence: 99%